New Host Record of Lutjanus gibbus for Parasitic Nerocila sp. (Crustacea, Isopo-da, Cymothoidae) from South Andaman, Andaman Islands, India - Pathan Anil; Paul Sayeri; Kadeparambil Arjunan Jayaraj (Journal of Tropical Life Science, 2019)
A new host of Cymothoid isopod, Nerocila sp. was identified from the dorsal surface of the body (caudal peduncle) of Lutjanidae fish Lutjanus gibbus (Forsskal, 1775) which is a new host record of isopod parasite Nerocila sp. from the coastal waters of South Andaman, Andaman Islands. This study revealed the first occurrence of this parasitic isopod (Nerocila sp.) from Andaman and Nicobar Islands. A comprehensive summary of the nominal Nerocila species recorded on different host species is provided. The present finding adds another species of isopod to the checklist of Andaman and Nicobar Islands.